श्रीअरविन्द के चिन्तन में चेतना की परामनोवैज्ञानिक अवधारणा - Krishna Choudhary (Dr. Chinmay Pandya, 2013)
श्रीअरविन्द के विचार में चेतना की परामनोवैज्ञानिक अवधारणा सर्वथा नये आयामों में प्रकट हुई है। चेतना के सन्दर्भ में उनके विचार भारतीय चिन्तनधारा की ही विस्तृत अभिव्यक्ति है। उनके चिन्तन में चेतना के विभिन्न प्रचलित अर्थों को नया स्वरूप मिला और उसके सूक्ष्म से सूक्ष्मतर स्तर की अभिव्यक्ति संभव हो सकी है। श्रीअरविन्द ने विशेष अर्थों में चेतना को चित्-शक्ति कहा है। उनकी चेतना संबंधी अवधारणा आधुनिक युग में भारतीय मनोविज्ञान का प्रतिनिधित्व करती है और साथ ही पाश्चात्य मनोविज्ञान से उसका गहरा अन्तर भी स्पष्ट करती है। श्रीअरविन्द ने मानव जीवन में मानस चेतना का बहुत महत्त्व बतलाया है। वे मानस चेतना को विश्व चेतना से जोड़ने वाली अनिवार्य कड़ी मानते हैं। मानस चेतना को मानव जीवन के रूपान्तरण एवं उध्र्व विकास का अनिवार्य एवं महत्त्वपूर्ण केन्द्र मानकर वे इसके सूक्ष्मतम पहलुओं को उजागर करते हैं। मानस के सूक्ष्म तलों की विवेचना ही उनके परामनोवैज्ञानिक विचारों का स्वरूप है। इस सन्दर्भ में श्रीअरविन्द मानस चेतना के अतीन्द्रिय चार लोकों की विवेचना करते हैं एवं आधुनिक मनोविज्ञान के लिए मानवीय मन के उच्च भागों में नयी संभावनाओं को तलाशने का मार्ग प्रशस्त करते हैं। मानस से अतिमानस के मध्य श्रीअरविन्द चेतना के विकास का विश्लेषण कर सर्वथा नई परामनोवैज्ञानिक अवधारणा की सृष्टि करते हैं। The ideological concept of consciousness has turned up into new facets in Sri Aurobindo's view. His thoughts are the noticeable expression of Indian notion with respect to the consciousness. Various prevalent connotations of consciousness got revamped in his philosophy and the expression of their subtlest level became feasible. Sri Aurobindo has addressed consciousness as Chit-Shakti in a notable sense. His concept of consciousness represents Indian psychology in the modern age and also rationalizes its profound differentiation from Western psychology. Sri Aurobindo has provided plenty of importance to human consciousness in an individual's life. They reckon human consciousness to be the connecting link with the universal consciousness. They underline human consciousness as an essential and paramount center by revealing its subtle aspects for the transformation and ascending evolution of human existence. The exploration of the subtle planes of the mind is the nature of their psychological perspective. In this context, Sri Aurobindo discusses the four realms of human consciousness and paves the way for modern psychology to explore new possibilities in the higher aspects of the human mind. Sri Aurobindo creates a new paradigmatic notion after analyzing the evolution of the psyche, from consciousness to super-consciousness.